Effect of organic acids on the preservation and feeding value of reconstituted milo - K.K. Bolsen; O.J. Cox; C.L. Drake (Kansas Agricultural Experiment Station Research Reports, 1972)
The use of high moisture grain in beef cattle rations has increased during the past several years. It has improved feed efficiency of high energy rations five to 20 percent in previous research. Non-nutritional advantages of high moisture grain include: (1) earlier harvest to lengthen the harvest season and/or free land for other uses; (2) fewer field losses from shattering lodging, wind and early frost and (3) no artificial drying.
Keywords: Cattlemen' s Day; 1972; Report of progress (Kansas State University. Agricultural Experiment Station); 557; Beef; Organic acids; Milo; Feed value